ROLE OF CHYMOTRYPSIN IN POST-OPERATIVE WOUND MANAGEMENT IN PATIENTS UNDERGOING ELECTIVE INGUINAL HERNIA REPAIR SURGERIES - FAROOQI, A; ZAHEER, F; ABBAS, S; SHAIKH, SN; SADIA, .; SALMAN, S (Biological and Clinical Sciences Research Journal, 2024)
This study aimed to evaluate the effectiveness of chymotrypsin and trypsin in improving post-operative wound management outcomes in patients undergoing inguinal hernia repair. Methods: An open-label randomised control trial was conducted at the Department of General Surgery, Ruth PFAU Civil Hospital Dow University of Health Sciences, Karachi. A total of 48 patients undergoing elective inguinal hernia surgery were included and randomly assigned to either Group A (placebo) or Group B (intervention). Group B received chymotrypsin (6 mg) and trypsin (1 mg) post-operatively for seven days. Outcome measures included oedema, hematoma, seroma, surgical site infection (SSI), pain scores, and duration of hospital stay. Data were analysed using SPSS version 21, with significance at P ≤ 0.05. Results: The mean age was higher in Group B (38.5 ± 11.1 years) than in Group A (33.91 ± 8.9 years) (P = 0.01). Group B had significantly lower incidences of oedema (42% vs 71%, P = 0.042), hematoma (21% vs 42%, P = 0.009), and seroma (11 vs 20, P = 0.007) compared to Group A. Although SSI rates were lower in Group B (25%) compared to Group A (50%), this difference was not statistically significant (P = 0.068). Pain scores were significantly lower in Group B (2.625 ± 0.7) compared to Group A (5.125 ± 0.7) (P < 0.0001). The duration of hospital stay was also shorter in Group B (3.75 ± 0.8 days) than in Group A (6.9 ± 1.08 days) (P < 0.0001). Conclusion: Chymotrypsin and trypsin significantly enhance post-operative recovery by reducing oedema, hematoma, seroma, pain scores, and hospital stay duration in inguinal hernia repair patients. These findings support incorporating enzymatic agents into post-operative care protocols to improve patient outcomes.